Long-term prognostic factors and outcomes in mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes: a clinical and biochemical marker analysis - Gao, Rui; Gu, Lihua; Zuo, Wenchao; Wang, Pan (Frontiers in Neurology, 2024)
BackgroundMELAS (Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-like episodes) is a common subtype of mitochondrial encephalomyopathy. However, few studies have explored the relationship between biochemical markers and prognosis. This study aimed to explore the relationship between clinical and biochemical markers and prognosis of patients with MELAS.MethodsThis was a retrospective single-center study. A total of 39 MELAS patients were followed for an average of 7.3 ± 4.7 (range 1–21 years). All patients underwent detailed demographic registration, neurological examinations, biochemical and mitochondrial DNA analyses, muscle biopsy. Throughout the follow-up period, the modified Rankin Scale (mRS) scores, recurrent strokes rates, and mortality were tracked.ResultsAll patients initially presented with stroke-like episodes. Of the 39 subjects who were followed, 8 died, primarily due to acute stroke-like episodes and status epilepticus. Univariate analysis showed a higher risk of mortality in patients with severe lactate elevation compared to those with normal and mildly elevated levels (OR = 5.714, 95% CI 1.086–30.071, p = 0.040). While the absence of anemia was associated with a lower risk of death compared to those with anemia (OR = 0.175, 95% CI 0.033–0.921, p = 0.040). In multivariate analysis, severe lactate elevation (OR = 7.279, 95% CI 1.102–48.086, p = 0.039) and anemia (OR = 0.137, 95% CI 0.021–0.908, p = 0.039) were identified as independent predictors of mortality. MRS scores were categorized as follows: 41% of patients scored 0 to 2, 38.5% scored 3 to 5, and 20.5% had a score of 6 or had died. There was a positive correlation between lactic acid levels and MRS scores (r = 0.460, p = 0.003). In contrast, hemoglobin levels were negatively correlated with MRS scores (r = −0.375, p = 0.015). Furthermore, a positive correlation was observed between MRS scores and the frequency of stroke-like episodes (r = 0.280, p = 0.042).ConclusionOur study found that the majority of patients with MELAS had poor clinical outcomes. Anemia and significantly increased lactate levels were identified as indicators of poor prognosis in MELAS. Early intervention may lead to improvements in clinical outcomes.